Transformation of Islamic Education: A Study of Changes in The Transformation of The Education Curriculum - Muh Ibnu Sholeh; Habibur Rohman; Eko Agus Suwandi; Akhyak; Nur Efendi; As'aril Muhajir (Jurnal Pendidikan Agama Islam, 2023)
Purpose – This study aims to identify the best implementation strategies in transformative Islamic education, explore transformative Islamic education activities that can inspire transformative learning, and analyze the transformation of Islamic education in Indonesia through curriculum transformation. Design/methods/approach – This research approach uses library research. Literature studies are obtained from various sources such as scientific journals, books, seminar papers, and related publications. The paradigm of data analysis in this research uses content analysis which includes data collection, reduction, presentation and drawing conclusions. Findings – The researchers obtained three findings in this study. First, there are two best implementation strategies when implementing transformative education: A). To offer critical thinking opportunities b). To offer opportunities to act from a new perspective. Second, there are five transformative educational activities that can inspire transformative learning, including: a). Job shadowing; B). Scenario-based education; C). Cultural adaptation in the workplace; D). Career change; and e). Establish cooperation with various educational institutions. Third, one of the education transformations that has been carried out in Indonesia is by transforming the curriculum starting in 1947, 1964, 1968, 1973, 1975, 1984, 1994, 1997, 2004, 2006, 2013, and current curriculum. The independent learning (self-regulated learning) curriculum has reached its 22nd episode Research Implications/Limitations – Data sources are limited to online and offline scientific literature. Future researchers can use in-depth interview and observation techniques to make the results more reliable Originality/value – The findings of this study provide an overview of implementation strategies and transformative Islamic education activities in a new perspective.